Association of CT perfusion and postoperative cognitive dysfunction after off-pump coronary artery bypass grafting. (2nd June 2016) - Song, Zhe; Fu, Paul; Chen, Mingying; Bi, Qi
Abstract : Objective : To investigate the relationship between an abnormal CT perfusion scan and postoperative cognitive dysfunction, as measured by changes in MoCA and MMSE scores, after off-pump coronary artery bypass grafting (OPCABG). Methods : Eight hundred and thirteen patients were selected who underwent OPCABG between August 2010 and September 2013. Cognitive function was assessed before operation and at seven days post-op. CT perfusion scan was obtained preoperatively and was used to divide patients into two groups: abnormal perfusion and normal perfusion groups. Results : (1) Logistic regression analysis showed that perfusion abnormalities (OR, 3.012; 95% CI, 1.660–5.463; P < 0.05) were an independent risk factor for postoperative cognitive dysfunction (POCD). (2) 556 patients with CT perfusion scans were divided into normal perfusion and abnormal perfusion groups: incidence of POCD in the abnormal perfusion group is significantly higher than the control group (21.6 vs 8.6%, P < 0.05); MMSE scores were significantly lower in patients with abnormal perfusion before and after surgery. MoCA scores demonstrated a significant drop after surgery for all patients with abnormal perfusion ( P < 0.05). The abnormal perfusion group had a significant reduction in the visuospatial/executive and naming scores in the MoCA as compared to normal perfusion ( P < 0.05). Conclusion : Abnormal CT perfusion is a significant risk factor for postoperative cognitive dysfunction, and has the most impact on visuospatial/executive and naming functions.